\(0,25x+175\%x=x+\dfrac{9}{7}\\ x\left(0,25+1,75\right)=x+\dfrac{9}{7}\\ 2x=x+\dfrac{9}{7}\\ \dfrac{9}{7}=2x-x=x\\ x=\dfrac{9}{7}\)
\(0,25x+175\%x=x+\dfrac{9}{7}\\ x\left(0,25+1,75\right)=x+\dfrac{9}{7}\\ 2x=x+\dfrac{9}{7}\\ \dfrac{9}{7}=2x-x=x\\ x=\dfrac{9}{7}\)
Tìm \(x\)
1. \(\dfrac{1}{7}=\dfrac{8}{-x}\)
2. \(\dfrac{3x}{9}=\dfrac{2}{6}\)
3. \(4\dfrac{2}{5}:\left(\dfrac{-33}{10}\right)+x=-1\dfrac{5}{6}\)
4. \(45\%.x-2\dfrac{3}{8}=-1\dfrac{31}{40}\)
5. \(\left(x-2\dfrac{1}{4}\right):\left(-\dfrac{5}{6}\right)=3\)
Đề bài : Tìm các số tự nhiên x
1 , \(\dfrac{2x+5}{x+1}\) 4 , \(\dfrac{3x+5}{x-1}\)
2 , \(\dfrac{2x+4}{x}\) 5 , \(\dfrac{3x+6}{x-1}\)
3 , \(\dfrac{2x+7}{x+1}\)
1. Tìm x, biết:
a, \(1\dfrac{3}{5}\) + \(\dfrac{\dfrac{2}{7}+\dfrac{2}{17}+\dfrac{2}{37}}{\dfrac{5}{7}+\dfrac{5}{17}+\dfrac{5}{37}}\) . x = \(\dfrac{16}{5}\)
b, (\(\dfrac{1}{24.25}\) + \(\dfrac{1}{25.26}\) + . . . + \(\dfrac{1}{39.40}\) ) . 120 + x. \(\dfrac{1}{3}\) = -4
c, \(\left|x-\dfrac{1}{3}\right|\) . 2 + \(\dfrac{4}{5}\) = 0,24
d, \(\dfrac{24}{7x-3}\) = \(\dfrac{-4}{25}\)
e, ( 50% x + \(5\dfrac{1}{4}\) ) , \(\dfrac{-2}{3}\) = \(2\dfrac{5}{6}\)
f, \(1\dfrac{1}{3}\) - 25%\(\dfrac{-5}{12}\) + 2x = 1,6 : \(\dfrac{3}{5}\)
0,25x - \(\dfrac{27}{8}\) x= \(\dfrac{-3}{4}\)
tìm x biết :
1.\(\dfrac{-5}{6}+\dfrac{8}{3}+\dfrac{-29}{6}\le x\le\dfrac{-1}{2}+2+\dfrac{5}{2}\)
2.\(\left(2,7x-1\dfrac{1}{2}x\right):\dfrac{2}{7}=\dfrac{-21}{4}\)
3.\(\left|2x-\dfrac{3}{4}\right|=1\)
làm hộ mik 3 con này cái
Tìm x biết :\(\dfrac{2x-5}{6}=\dfrac{x-7}{5}\)
\(\dfrac{4x+1}{3}=\dfrac{2x-3}{4}\)
x : \(\dfrac{2}{3}\) = 150 \(\dfrac{35}{9}\) : x = \(\dfrac{35}{6}\)
\(\dfrac{49}{7}\) : x =\(\dfrac{49}{5}\)
1 - { 5\(\dfrac{4}{9}\) + x - 7\(\dfrac{7}{18}\) }: 15\(\dfrac{3}{4}\) = 0
2. tìm x
a. \(\dfrac{x}{8}\)=\(\dfrac{-9}{6}\)
b. \(\dfrac{4}{9}\)+\(\dfrac{7}{3}\):x=\(\dfrac{1}{5}\)
c. \(\dfrac{-5}{9}\)- x=\(\dfrac{4}{3}\)
d. x +\(\dfrac{4}{17}\)=\(\dfrac{2}{34}\)
e. \(\dfrac{3}{4}\).x=\(\dfrac{7}{8}\)
f. \(5\dfrac{4}{7}\): x=11
1: \(\dfrac{2\cdot\left(x+2\right)}{3}-\dfrac{5\cdot\left(x-1\right)}{4}=\dfrac{3\cdot\left(5-x\right)}{2}-1\dfrac{1}{2}\cdot\left(2x+3\right)\)